A Thematic Analysis of the Painting, "Two Conflicting Sages" attributed to Aqa Mirak in Khamsa Tahmasbi: An Iconological Approach - Sahand Allahyari; Morteza Afshari; Khashayar Ghazizadeh (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
The painting "Two Conflicting Sages" attributed to Aqa Mirak in Khamsa Tahmasbi's edition is one of the works in which the painter, as the author, has created an additional meaning out of the original work. The purpose of the present paper is to identify the hidden layers of meaning in this painting. To do so, the research employs the framework of Panofsky's iconology via a descriptive analytical method. The paper seeks to find out which hidden layers of meaning exist in the painting. The results show that the painting has originated from spiritual and religious beliefs, particularly those of Islamic wisdom. Agha Mirak, being both influenced by this mystical view and being closely connected to Shah Tahmasb's court, while showing the splendor and majesty of the court with the help of visual symbols, has portrayed the conflict of the two sages in the court scene, and thereby, has reflected moral messages to the king and the courtiers in an esoteric and indirect way, lest their excessive prejudices cause the destruction of the monarchy. The image represents the key conflict between the reason and illusion, a conflict which exists within all human beings and leads to pride and neglect. Illusion is like a beautiful flower whose appearance is agreeable to reason, but in reality, it leads to human failure.